THE EFFECT OF COMMUNICATION, WORK DISCIPLINE AND INNOVATIVE WORK BEHAVIOR ON EMPLOYEE PERFORMANCE AT PT. MEGA FINANCE PEKANBARU - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan, 2026)
This study aims to determine the effect of communication, work discipline and innovative work behavior on employee performance at PT. Mega Finance Pekanbaru. The population in this study were employees at PT. Mega Finance Pekanbaru with a total of 30 employees. Thus, the number of samples in this study was 30 respondents. The analysis method in this study was multiple linear regression analysis using IBM SPSS19 software. The results of the study obtained Communication, has a positive and insignificant effect on employee performance and Work Discipline and Innovative Work Behavior have a positive and significant effect on Employee Performance. The achievement of the goals set by the company cannot be separated from human resources. Therefore, the company must pay attention to what factors can improve employee performance, so that employees can work optimally.